2015
DOI: 10.1016/j.ijbiomac.2015.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Purification and primary structure of a novel mannose-specific lectin from Centrolobium microchaete Mart seeds

Abstract: This study aimed to purify and characterize a novel mannose-binding lectin from the seeds of Centrolobium microchaete. Centrolobium microchaete lectin (CML) was purified by affinity chromatography in mannose-Sepharose-4B column. CML agglutinated rabbit erythrocytes and was inhibited by D-mannose, α-methyl-D-mannoside, D-glucose, N-Acetyl-D-glucosamine and sucrose. The lectin was stable at pH 7.0 and 8.0 and temperatures up to 60°C. The monomeric form of CML showed approximately 28kDa, and its native form is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
1
8
1
Order By: Relevance
“…The results are shown in Table 2. Similar results were reported for lectins from Platymiscium floribundum [16], Centrolobium microchaete [18] and Canavalia virosa [37]. Lis and Sharon [38] revealed that trypsin can be used to modify the erythrocytes surface to enhance its affinity for lectins without affecting the total number of lectin binding sites on the erythrocytes.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The results are shown in Table 2. Similar results were reported for lectins from Platymiscium floribundum [16], Centrolobium microchaete [18] and Canavalia virosa [37]. Lis and Sharon [38] revealed that trypsin can be used to modify the erythrocytes surface to enhance its affinity for lectins without affecting the total number of lectin binding sites on the erythrocytes.…”
Section: Resultssupporting
confidence: 77%
“…POSL belongs to the mannose/glucose specificity group of lectins from Dalbergieae tribe, which has specificity for different sugars. Among well studied member of the tribe that belong to mannose/glucose specificity group are lectins from Pterocarpus angolensis [3], Platymiscium floribundum [16], Centrolobium microchaete [18], and Platypodium elegans [40]. Though, other members of the tribe that have specificity for other carbohydrates especially galactose have also been reported (Vatairea marcocarpa [11]; Lonchocarpus capassa [14]; Vatairea guianensis [15]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbohydrate content and glycosylation nature of Hyacinth bulb lectin was determined by anthrone assay and PAS staining respec- tively. The carbohydrate content of purified lectin was found to be 5.2% and according to literature carbohydrate content of lectin vary from 1.5 to 16% [33,34]. PAS stain result indicated that hyacinth lectin was glycoprotein in nature ( Fig.…”
Section: Carbohydrate Content and Glycosylation Nature Of Hyacinth Lementioning
confidence: 61%
“…For these lectins, SDS-PAGE profile was similar to other mannose lectins, a band around 30 kDa with an isoelectric point near to 6.5, and they were able to agglutinate human RBCs from A, B, and O donors. This means that specificity by mannose/glucose moieties or mannose-rich glycan is not a unique feature of any family; conversely, species such as Galanthus nivalis (tribe Galantheae) [105] and Centrolobium microchaete (tribe Dalbergieae) [106], among others, even species from other families such as Moraceae have mannose/glucose lectins [107]. Galactia lindenii lectin type -I (GLL-I) [77].…”
Section: Fabaceae (Legume) and Lamiaceae (Mint) Lectinsmentioning
confidence: 99%